Perkembangan Penelitian Penggunaan Artificial Intelligence di Perpustakaan Berbasis Data Scopus - Tupan, Tupan (Perpustakaan Nasional, 2024)
This study aims to analyze the development of AI use in libraries with bibliometric methods based on Scopus data. The study uses bibliometric analysis methods. Data were collected from the Scopus database using the keywords (Artificial intelligence OR AI) AND (Library